Anthocyanins from ornamental flowers of red frangipani, Plumeria rubra - Byamukama, Robert; Namukobe, Jane; Jordheim, Monica; Andersen, Øyvind M.; Kiremire, Bernard T. (Scientia Horticulturae, 2011)
Two anthocyanins were isolated from ornamental reddish flowers of Plumeria rubra L. (Apocynaceae) by a combination of chromatographic techniques. Their structures were elucidated mainly by the use of homo- and heteronuclear nuclear magnetic resonance spectroscopy and high-resolution electrospray mass spectrometry. The anthocyanin cyanidin 3-O- -(2 -glucopyranosyl-O- -galactopyranoside) (75%), has previously been isolated only from Cornus suecica (Cornaceae) fruits, while the other (20%) was identified as cyanidin-3-O- -galactopyranoside. This is the first report of the anthocyanins responsible for the attractive colours of the flowers of red frangipani.
Keywords: Red frangipani; Plumeria rubra L.; Apocynaceae; Ornamental colour; Anthocyanins; Cyanidin 3-O- -(2 -glucopyranosyl-O- - galactopyranoside)